Does chlorella vulgaris modulate the expression of COL and MMP Genes in skin ageing? - Loke CY,; Nur Hidayah MS,; Mohd Fadhli MF,; Teo SK,; Nor Hidayah AG,; Yasmin Anum MY,; Suzana M, (Penerbit UKM, 2010)
Chlorella vulgaris, a unicellular microalgae, produces many intracellular phytochemicals namely carotenoids, tocopherols, ubiquinone and protein. Skin ageing which is induced by oxidative stress involves decreased extracellular matrix synthesis and increased expression of enzymes that degrade the collagenous matrix. The objective of this study was to determine the effect of C. vulgaris on the expression of genes encoded for collagen (COL) and matrix metalloproteinases (MMPs) which are involved in skin ageing. Human diploid fibroblasts (HDFs) were obtained from circumcision foreskin of 8-12 year-old boys. HDFs were cultured into 3 groups: untreated control cells, cells with stress-induced premature senescence (SIPS; cells were induced with H2O2 at passage 6 for 2 weeks) and SIPS treated with C. vulgaris (prolonged C. vulgaris treatment started at passage 4 and combined treatment with H2O2 at passage 6 for 2 weeks). Senescence-associated ß-galactosidase (SA ß-gal) was determined using senescent cells histochemical staining kit (Sigma, USA). Expression of COLI, COLIII, COLIV, MMPI, MMPII and MMPIII genes was quantitatively analysed with real-time RT-PCR method (iScript™ One Step real-time PCR with SYBR® Green; Biorad). HDFs treated with H2O2 (SIPS) exhibited senescent morphological features of flattening and enlarged with increased expression of SA ß-gal (p<0.05). Gene expression analysis showed COLI was downregulated in SIPS and SIPS treated with C. vulgaris (p<0.05) while COLIII decreased in SIPS and increased in SIPS treated with C. vulgaris (p<0.05). Expression of MMPI was increased in SIPS and SIPS treated with C. vulgaris (p<0.05) indicating its synergistic effect with H2O2 treatment. In conclusion, in skin ageing, COLI and COLIII genes were downregulated while MMPI was upregulated. C. vulgaris modulated the expression of COL and MMP genes by downregulating COLI and upregulating COLIII and MMPI but it did not exert anti-ageing effect.